Polymorphisms in the XRCC1 gene modify survival of bladder cancer patients treated with chemotherapy. Issue 8 (25th April 2013) - Sacerdote, Carlotta; Guarrera, Simonetta; Ricceri, Fulvio; Pardini, Barbara; Polidoro, Silvia; Allione, Alessandra; Critelli, Rossana; Russo, Alessia; Andrew, Angeline S.; Ye, Yuanqing; Wu, Xifeng; Kiemeney, Lambertus A.; et al.
Abstract : Survival of bladder cancer patients depends on several factors including disease stage and grade at diagnosis, age, health status of the patient and the applied treatment. Several studies investigated the role of DNA repair genetic variants in cancer susceptibility, but only few studies investigated their role in survival and response to chemotherapy for bladder cancer. We genotyped 28 single nucleotide polymorphisms (SNP) in DNA repair genes in 456 bladder cancer patients, reconstructed haplotypes and calculated a score for combinations of the SNPs. We estimated Hazard Ratios (adjHR) for time to death. Among patients treated with chemotherapy, variant alleles of five SNPs in the XRCC1 gene conferred better survival (rs915927 adjHR 0.55 (95%CI 0.32–0.94); rs76507 adjHR 0.48 (95%CI 0.27–0.84); rs2854501 adjHR 0.25 (95%CI 0.12–0.52); rs2854509 adjHR 0.21 (95%CI 0.09–0.46); rs3213255 adjHR 0.46 (95%CI 0.26–0.80). In this group of patients, an increasing number of variant alleles in a XRCC1 gene score were associated with a better survival (26% decrease of risk of death for each additional variant allele in XRCC1 ). By functional analyses we demonstrated that the previous XRCC1 SNPs confer lower DNA repair capacity. This may support the hypothesis that survival in these patients may be modulated by the different DNA repair capacity determined by genetic variants. Chemotherapy treated cancer patients bearing an increasing number of "risky" alleles in XRCC1 gene had a better survival, suggesting that a proficient DNA repair may result in resistance to therapy and shorter survival. This finding may have clinical implications for the choice of therapy. Abstract : What's new? While several studies have investigated the role of DNA repair genetic variants in cancer susceptibility, only few investigated their role in survival and response to chemotherapy for bladder cancer. The present study looked at the association between 28 SNPs in eight DNA repair genes and survival from bladder cancer in 456 bladder cancer patients. When receiving chemotherapy, patients who presented a higher number of genetic variants in the XRCC1 base‐excision repair gene had a better survival, suggesting that proficient DNA repair results in resistance to therapy and shorter survival. This finding may have clinical implications for the choice of therapy.